2017
DOI: 10.2967/jnumed.117.189605
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Cancer Treatment Response by 18F-FDG PET/CT: Multicenter Assessment of Measurement Variability

Abstract: The aim of this study was to assess the interobserver variability of quantitative 18 F-FDG PET/CT parameters used in assessments of treatment response across multiple sites and readers. Methods: Paired pre-and posttreatment 18 F-FDG PET/CT images of 30 oncologic patients were distributed to 22 readers across 15 U.S. and international sites. One reader was aware of the full medical history (read reference ) of the patients, whereas the 21 other readers were unaware. The readers selected the single hottest tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The variance of SUVs could be greater in clinical practice compared to ideal study setting [ 16 ]. In the clinical setting, measurement of SUV max was demonstrated to have high agreement in our previous paper, while the statistically more robust SUL peak showed suboptimal agreement [ 9 ]. We wanted to know whether using uniform software could eliminate the variability associated with the computation differences for SUL peak across multiple vendors and software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variance of SUVs could be greater in clinical practice compared to ideal study setting [ 16 ]. In the clinical setting, measurement of SUV max was demonstrated to have high agreement in our previous paper, while the statistically more robust SUL peak showed suboptimal agreement [ 9 ]. We wanted to know whether using uniform software could eliminate the variability associated with the computation differences for SUL peak across multiple vendors and software.…”
Section: Discussionmentioning
confidence: 99%
“…Sites both with National Cancer Institute Quantitative Imaging Network affiliation and without which did not participate in the previous study with the same data set were recruited by e-mail and conference calls. The dataset was the based on a previous study of reader variability [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…This correlates well with our results, although, they did not have a longitudinal study design. Other studies have shown for various types of cancer that raters generally achieved 'moderate agreement' for qualitative visual assessment [25][26][27], and 'almost perfect agreement' for quantitative assessment when measuring the standardized uptake value (SUV) [28][29][30][31][32]. This supports that SUV (from which SUL is derived) is a robust variable to measure; therefore, the discordance in interrater agreement for PERCIST is likely due to the qualitative judgment (detection of new foci or unequivocal progression) of the raters.…”
Section: Discussionmentioning
confidence: 99%